Tillsyn bortom gränserna - Gränsöverskridande tillsyn eller symbolisk kontroll enligt Corporate Sustainability Due Diligence Directive? - Rönnkvist Oxelman,Emilia (2025)
The European Union’s efforts to promote sustainable development have been brought to a critical point with the establishment of the Corporate Sustainability Due Diligence Directive (CSDDD). By requiring that due diligence be ensured throughout the entire value chain, high expectations are placed on EU companies and their business partners. Compliance with due diligence has proven particularly challenging in the extraction of raw materials in third countries, while the EU remains a dominant importer. As part of the implementation of the CSDDD, Member States are required to establish national supervisory authorities tasked with reviewing compliance within the value chains of domestic companies. This raises questions concerning corporate obligations and how the supervisory mechanism under the Directive can, in practice, examine due diligence. The purpose of this thesis is to analyse the extent to which the supervisory provisions of the CSDDD, with particular focus on Articles 24–25, enable oversight of compliance with due diligence requirements in EU companies’ value chains outside the EU. The thesis is conducted using a legal-dogmatic and EU law methodology and is based primarily on EU legal sources, relevant doctrine, and international soft law instruments. The analysis demonstrates that the CSDDD imposes extensive obligations on companies to identify, prevent, and remedy adverse impacts throughout the entire value chain, including among indirect business partners in third countries. Supervisory authorities are, however, to a large extent dependent on companies’ own reporting, which hampers the ability to detect and address serious violations and increases the risk of superficial compliance. The absence of a more centralised and harmonised framework for the conduct of supervision further reinforces the risk of fragmented implementation among Member States. In conclusion, the CSDDD has the potential to strengthen the protection of human rights and the environment in global value chains, including in relation to indirect business partners in third countries. However, the Directive’s impact is dependent on the resources of supervisory authorities, their future choice of instruments, and access to effective cooperation mechanisms. In the absence of such prerequisites and clearer central regulation, supervision risks assuming a largely symbolic function, rather than ensuring proportionate and risk-based due diligence where risks are most significant.
Keywords: EU-rätt; CSDDD; Offentlig tillsyn; Corporate Sustainability Due Diligence